The Role of Neutrophils and Neutrophil Extracellular Traps in Acute Pancreatitis - Wan, Jianhua; Ren, Yuping; Yang, Xiaoyu; Li, Xueyang; Xia, Liang; Lu, Nonghua (Frontiers in Cell and Developmental Biology, 2021)
Leukocyte invasion (neutrophils and monocytes/macrophages) is closely related to the severity of acute pancreatitis (AP) and plays an important role in the systemic inflammatory response and other organ injuries secondary to AP. Increased and sustained activation of neutrophils are major determinants of pancreatic injury and inflammation. After the onset of AP, the arrival of the first wave of neutrophils occurs due to a variety of triggers and is critical for the exacerbation of inflammation. In this review, we summarize the functional characteristics of neutrophils, elastase and heparin-binding proteins in granules, the mechanisms of neutrophil recruitment and the role of neutrophil extracellular traps (NETs) in AP.